The Duty to Protect, Abortion, and Organ Donation - Carroll, Emily (Cambridge quarterly of healthcare ethics, 2022)
Some people oppose abortion on the grounds that fetuses have full moral status and thus a right to not be killed. We argue that special obligations that hold between mother and fetus also hold between parents and their children. We argue that if these special obligations necessitate the sacrifice of bodily autonomy in the case of abortion, then they also necessitate the sacrifice of bodily autonomy in the case of organ donation. If we accept the argument that it is obligatory to override a woman’s bodily autonomy for the sake of an unborn child’s survival, we must continue to override the bodily autonomy of parents to ensure the survival of their living children, until the parent no longer has a special obligation to their child to the same degree as their special obligation to the fetus. And if the life of a child is truly more important than the bodily autonomy of its parents, as must be the case to force women to carry unwanted pregnancies to term, this should remain true until such a time that their children are no longer considered their responsibility. Thus, parity of reasoning suggests that policies compelling the gestation of a fetus should be accompanied by policies compelling organ donation.